Characteristic Phenotype and Growth of Chicken Layer Strain (Gallus gallus domesticus, Linnaeus 1758) - Feren Putri Sholiha; Galy Hardyta; Budi Setiadi Daryono (Berkala Ilmiah Biologi, 2022)
The aim of this research is to study the phenotypic character and growth of layered chickens. In this study, crosses between G4 Layer chickens were carried out which resulted in G5 Layer chickens. Morphological characters, growth weights and measuring the feed-conversion ratio (FCR) were observed. The results obtained were 10 individuals of G5 Layer chickens with the proportion of male gametes (70%) and female gametes (30%). Phenotypic characters are brown fur color and a combination of brown and white. The value of Feed Conversation Ratio (FCR) is 1.67 and the average weight growth of G5 Layer chickens reaches 491.2 grams at the age of 7 weeks.